دور الرقابة المالية القبلية في حماية وترشيد النفقات العمومية - حساسة, عبد المالك; حملاوي, عبد الرزاق; مولاي, حفصية (جامعة الوادي university el-oued, 2022)
لاشك بأن الرقابة السابقة للإلتزام بالنفقات العمومية يهدف اساسا الى الحيلولة دون التجاوزات المالية بكل انواعها، وتمنع من الوقوع في أي خطأ الذي يترتب عليه اضرار تمس المال العام ، لهذا الأساس يعتبر هذا النوع من الرقابة المالية القبلية ذات اهمية بالغة من خلال الدور الذي تلعبه تلك الاجهزة الرقابية، بمختلف مصالحها حيث تسهر على توظيف النفقات العمومية مطابقة مع التنظيمات والقوانين الساري العمل بها وعليه يمكن القول بأن الرقابة المالية القبلية ا والسابقة على النفقات بمثابة رقابة وقائية تمكننا من اكتشاف الاخطاء والاختلالات وتصحيحها قبل قبل الشروع في صرف النفقة ا وتنفيذها . كما يهدف هذا النوع من الرقابة الى لفت انتباه الآمرين بالصرف لخطأهم سواء اكان بحسن النية ا وسوء النية، والادراج القانوني الصحيح للنفقة وفقا لسياسة دولة المعتمدة والمسطرة لحماية وترشيد النفقات من الإختلاسات، وبمأن الرقابة المالية السابقة تعرف إداريا بالمراقب المالي الذي أحطناه بكل الجوانب من خلال تعريفه ومهامه ومسؤليته ومجالات تدخله واستنتجنا من كل ذالك بأن الرقابة التي يمارسها المراقب المالي تقتصر على الجانب الشكلي للنفقة،ولعل الإستثناءات الواردة على مهامه والممثلة في تلك الإلتزاماتالإحتياطية المنصوص عليها بموجب قوانين وتشريعات محددة لكيفيات العمل بها، دون ان تتعدى الى رقابة الملائمة، التي تفحص العمليات المالية من بدايتها الى غاية نهايتها هذا من جهة . ومن جهة اخرى نجد ان رقابة المحاسب العمومي والتي هي رقابة متزامنة مع سيرورة النفقات ،اي يمارس رقابة سابقة في شقها القبلي،ورقابة انية وبعدية لأنه العون المكلف قانونا بالتحصيل وبدفع النفقات العمومية الى وجهتها الصحيحة وتحت مسؤوليته الشخصية في التحصيل ا والأنفاق العام الذي يتم على مستوى مصالحه. There is no doubt that the previous control over the commitment of public expenditures aims mainly at preventing financial abuses of all kinds, and preventing them from falling into any error that would result in damage to public money. The supervisory authority, with its various interests, as it ensures the employment of public expenditures in accordance with the regulations and laws in force, and accordingly it can be said that the prior or prior financial control over expenditures is a preventive control that enables us to discover errors and imbalances and correct them before proceeding to disbursement or implementation of the alimony.This type of control also aims to draw the attention of those who ordered the exchange to their mistake, whether in good faith or bad faith, and the correct legal inclusion of alimony in accordance with the approved and established state policy to protect and rationalize expenditures from embezzlement, and since the previous financial control is known administratively by the financial controller that we have covered in all aspects through his definition Its tasks, responsibilities, and areas of intervention. We concluded from all of this that the control exercised by the financial controller is limited to the formal aspect of the expenditure, and perhaps the exceptions to his tasks and represented in those precautionary obligations stipulated under specific laws and legislation for the working methods, without transgressing to the appropriate control, which examines operations Finance from its beginning to its end.On the other hand, we find that the public accountant’s control, which is a simultaneous control with the expenditure process, i.e. exercises previous control in its tribal part, and immediate and remote control because he is the legally mandated assistant to collect and pay public expenses to their correct destination and under his personal responsibility in the collection or public spending that takes place at the level of his interests.
مذكرة ماستر
Keywords: الرقابة المالية .السابقة . النفقات العمومية . المراقب المالي . المحاسب العمومي.: contrôle financier. précédent .dépenses publiques. Contrôleurfinancier .Trésor public.